Transforming growth factor-β1 and runt-related transcription factor 2 as markers of osteogenesis in stem cells from human exfoliated deciduous teeth enriched bone Grafting - Chiquita Prahasanti; Noer Ulfah; Ivan Indra Kusuma; Nur Hayati; Diah Savitri Ernawati; Agung Krismariono; Taufan Bramantoro (Wolters Kluwer Medknow Publications, 2018)
Background: Stem cells from human exfoliated deciduous teeth (SHED) are one source of adult stem cells which can proliferate and differentiate into many types of tissues than any other stem cells. SHED represent potential stem cells for therapeutic therapy and tissue engineering. Aims: The aim of this study was to compare the expression of transforming growth factor-β1 (TGF-β1) and runt-related transcription factor 2 (RUNX2) in hydroxyapatite (HA) scaffold with SHED. Subjects and Methods: Eight experimental animals were divided into two groups. The first group was transplanted with HA and the second with HA and SHED. The expression of TGF-β1 and RUNX2 was seen 21 days later by means of immunohistochemical analysis. Statistical Analysis Used: Data were analyzed using an independent t-test with a significance level of 5%. Results: The analysis results of an independent t-test showed a significant difference between the two groups. The second group given HA with SHED showed a significantly higher expression of TGF-β1 and RUNX2 than that of the first group. Conclusions: Expression of TGF-β1 and RUNX2 occurs after the application of HA with SHED, while TGF-β1 and RUNX2 expression in the HA with SHED group was significantly higher than in the group without SHED.